Primary osteoarthritis of the elbow. Issue 9 (September 1989) - Doherty, M; Preston, B
Abstract : Sixteen patients (14 male, two female; mean age 61, range 49-75 years) with elbow osteoarthritis (OA) unassociated with nodal or crystal related OA were studied. None had received obvious trauma. The dominant elbow was affected in 14, the other in 12 (mean symptom onset in these 26 elbows 53 years (range 31-63), mean symptom duration 7 year (range 1-20]. Joint fluids (six patients) were non-inflammatory: biopsy (two) showed non-specific synovitis. Radiographic changes occurred in humeroulnar (25/26, 96%), humeroradial (100%), and radioulnar (22/26, 85%) compartments: uniform narrowing with hypertrophic change predominated and osseous bodies were common (18/26, 69%). Thirteen had OA elsewhere, notably 2nd/3rd metacarpophalangeal joints (10/16, 62%), knees (6/16, 38%), and hips (5/16, 31%). A good clinical outcome was observed in 22/26 elbows. In our experience symptomatic 'primary' OA of the elbow particularly affects middle aged men, commonly associate with metacarpophalangeal OA ('Missouri metacarpal syndrome'), and has a favourable outcome. Contrary to previous reports a major role for trauma is difficult to substantiate.